CAN RESILIENCE BE A COPING STRATEGY TO REDUCE ACADEMIC BURNOUT? STUDY ON ACCOUNTING EDUCATION STUDENTS - Fauzan, Slamet; Permata, Detria Putri Firda (Universitas Muhammadiyah Surakarta, 2025)
This study, designed to examine the moderating role of resilience in the effect of academic stress on academic burnout, which is triggered by role stressors. This study applied the Psychological Stress and Coping Theory. The demographic and sample for this study were Accounting Education students at the State University of Malang. This study employed a quantitative research design using a cross-sectional survey method. Data were gathered by distributing questionnaires and analyzed using Structural Equation Modeling (SEM) using Smart PLS 4, which allows for the measurement of the moderating effect. The findings revealed resilience as a moderating variable on the influence of academic stress on academic burnout could not be proven, indicating that resilience did not function as an effective coping strategy to reduce academic burnout. Role stressors had a significant positive effect on academic burnout, role stressors had a positive effect on academic stress, academic stress had a significant positive effect on academic burnout, indirectly academic stress can significantly mediate the influence of role stressors on academic burnout using the partial mediation category. The benefits of this study include providing information to educational institutions on how to design and administer intervention programs that promote student resilience development.